Sounds great - Beisbier, Beverly (Heinle & Heinle, 1994)
SOUNDS GREAT teaches learners to discover, recognize, and use American English word stress, sentence stress, intonation patterns, and high-frequency vowels and consonants. The many guided conversations, pair and small group practices, information gap activities, peer interviews, and short oral reports invite students to enjoy improving their command of spoken English.